Factors Affecting Immunization Coverage for Children Under Five Years in Rwanyamahembe Sub-County, Mbarara District- Uganda. - Omia, Santos (Kabale University, 2023)
The study was focusing on the factors affecting immunization coverage for children under five years taking Rwanyamahembe sub-county, Mbarara district as a case study. The specific objectives were to; determine the level of expanded program on immunization (EPI) service coverage, identify socio-demographic and institutional factors affecting with EPI service coverage. The study adopted cross- sectional study design employing a quantitative approach for data collection. Information was gathered from 120 respondents using questionnaire and interview guide. Data was analyzed using SPSS version 18 to generate both descriptive and regression statistics. The study found out the level of expanded program on immunization (EPI) service coverage to be relatively low as evidenced by few respondents who had children that are fully vaccinated as compared to majority who did not complete vaccination. The study also identified socio-demographic factors affecting EPl service coverage in the area such as lack of information about immunization, age of the mother/guardian. level of education. negative experiences with immunisation, possession of vaccination cards, sex of the child and accessibility of vaccination sites. The study further identified inadequate funding of the program, perceived shortage of staff, cost of vaccination and vaccination cards, inadequate supply of vaccine stock, inadequate vaccination sites and corruption and embezzlement of funds as the main institutional factors affecting with EPI service coverage. As a result of the significant results, the study concludes that EPI service coverage in Rwanyamahembe sub-county is low due to different socio-demographic and institutional factors. It therefore recommends the provision of vaccine related targeted health education to mothers at home and during ANC visits is an effective strategy to improve immunization completion rates in low literacy and income settings. Supervision of immunization activities by the district EPI focal person. This is key in identifying gaps during static and outreach programs. Emphasis on vaccinators arriving on time and all services given to mothers without a cost.